Non-tradables in Brazilian economic history - Eustáquio José Reis (EconomiA, 2023)
Purpose: The purpose is to market a reinterpretation of Brazilian economic history highlighting the importance of non-tradable goods to understand major historical developments such as the lack of industrialization in the mining boom; the rise and contribution of industries to development in the early 20th century; indexation as hyperinflation in the late 20th century; growth and cycles in the early 21st century. Design/methodology/approach: Section 2 introduces analytical perspectives on the relationship between non-tradables, transport costs and external shocks. Section 3 presents a historical overview of the gold and coffee cycles in the Brazilian economy, which highlights the crucial role played by transport costs in the genesis of industrialization. Thus, in a more precise way, industrialization was not an import substitution process but the substitution of non-tradables by the domestic tradable manufactures. Findings: Section 4 shows that Brazilian statistical records and historiography disregard this characterization and, to that extent, underestimate economic growth in the primary export phase (1872-1920) and overestimate growth rates in the industrialization period (1920-1940). Section 5 shifts to the end of the 20th century to analyze the relationship between non-tradables, indexation and hyperinflation. Section 6 concludes with a brief discussion of the role played by the terms of trade and non-tradables in the unfolding of the 2014 economic crisis. Originality/value: Distance from international markets and a continental geographic size made transport costs in Brazil historically prohibitive: the relevance of non-tradables in the Brazilian economic history. While the theme is not new, it seldom received proper attention in the historiography.
Keywords: 330; Brazil; History; Crisis; Industrialization; Hyperinflation; Non-tradables